2017
DOI: 10.1039/c7ra04814a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite identification and pharmacokinetic study of platycodi radix (Jiegeng) in vivo

Abstract: The secondary platycosides, 3-O-β-d-glucopyranosylplatycodigenin and 3-O-β-d-glucopyranosylplatyconic acid, were qualitatively and quantitatively analyzed in vivo for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…GPD 682 (128.5 mg, 4.76%) and 3- O -β-D-glucopyranosyl platyconic acid (GPA 696 ) (15.9 mg, 0.59%) were obtained by flash chromatography (Biotage, Sweden), with ternary gradient elution (CH 2 Cl 2 :MeOH:H 2 O). GPD 682 was obtained at CH 2 Cl 2 :MeOH:H 2 O = 8:2:0.2, and GPA 696 was obtained at CH 2 Cl 2 :MeOH:H 2 O = 9.5:3:0.4 (Tang et al, 2017). The NMR and HRMS were described in the supporting information ( Figures S1−S8 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPD 682 (128.5 mg, 4.76%) and 3- O -β-D-glucopyranosyl platyconic acid (GPA 696 ) (15.9 mg, 0.59%) were obtained by flash chromatography (Biotage, Sweden), with ternary gradient elution (CH 2 Cl 2 :MeOH:H 2 O). GPD 682 was obtained at CH 2 Cl 2 :MeOH:H 2 O = 8:2:0.2, and GPA 696 was obtained at CH 2 Cl 2 :MeOH:H 2 O = 9.5:3:0.4 (Tang et al, 2017). The NMR and HRMS were described in the supporting information ( Figures S1−S8 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has a long medicinal history and is often used as an adjunct in treatment of respiratory disease (Yim et al, 2016), and a recent study revealed that PG could affect the distribution of glycyrrhetinic acid in organisms (Cui et al, 2018). Pharmacokinetic studies have shown that saponins in PG are quickly metabolized into secondary saponin metabolites (SSM) in the body and then produce pharmacological effects (Tang et al, 2017), and it has been indicated that SSM might be the main medicinal substance (Lorent et al, 2014). Although dozens of active SSM have been reported in PG, few previous studies have revealed the specific compounds that exert the activity.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, metabolic studies showed that the total saponins of Jiegeng were broken down in the gastrointestinal tract. GP-682 and the platycodon secondary saponin 3-O-β-d-glucopyranosylplatyconic acid 696 (GPA-696) were the main metabolites [16]. GP-682 had better biological activity than GPA-696 in our previous study [17], which helped increase drug delivery to the lung tissue.…”
mentioning
confidence: 90%
“…The PSS of GP-682 and GPA-696 were isolated and purified from a total saponin extract of platycodi radix [16]. The preparation process was based on our previously published paper [17].…”
Section: Separation and Purification Of Pssmentioning
confidence: 99%
“…In recent years, an integrative strategy using ultra-highperformance liquid chromatography coupled with quadrupole time-of-ight mass spectrometry (UPLC-Q-TOF-MS) combined with ultra-high-performance liquid chromatography with triple quadrupole mass spectrometry (UPLC-QqQ-MS) has been widely used to identify the absorbed constituents and determine main compounds in complex matrices. [7][8][9][10][11] Hence, they are valuable analytical techniques for identifying key compounds and evaluating the pharmacokinetics of TCM formulae in vivo.…”
Section: Introductionmentioning
confidence: 99%